Influence of Italian ryegrass (Lolium multiflorum Lam.) as intercrop with spring barley (Hordeum vulgare L.) on the diversity of weed communities - Krzysztof Orzech; Maria Wanic (Acta Agrobotanica, 2014)
The paper presents results of 3 years of studies (2009–2011) on the influence of Italian ryegrass on the development of weed communities in spring barley (without chemical weeds control) cultivated after potato, spring wheat and spring barley. The reaction of spring barley to the choice of the forecrop was compared with identical plots with pure stand of that cereal where herbicides were applied for weeds control. Evaluation of infestation with weeds was conducted during barley tillering and before harvest. That evaluation considered the number and composition of weed species. During harvest, the dry mass of weeds was also considered. The results were used for determination of Shannon-Wiener diversity index and species homogeneity coefficient, Simpson’s index of dominance as well as Sørensen similarity index. Spring barley weeding was significantly higher in case of cultivating it in mixed stand with Italian ryegrass (without chemical control), than in pure stand (with control). In the plots with mixed crop, lower diversity and homogeneity of weeds’ communities were recorded than in pure stand. Barley in mixed crop sown after spring barley, during both times of evaluation (spring and before harvest), increased the value of the index of dominance according to the number of species the most. As concerns the composition of species, number and biomass, the communities of pure stand and mixed crop with Italian ryegrass on the plot after potato were the most similar.